Pelindungan Hukum terhadap Minuman Alkohol Tradisional Khas Indonesia (Legal Protection towards Indonesian Traditional Alcoholic Beverages) - Cita Yustisia Serfiyani; Iswi Hariyani; Citi Rahmati Serfiyani (Jurnal Negara Hukum: Membangun Hukum Untuk Keadilan, 2020)
Traditional alcoholic beverages have existed in Indonesian culture and society for various purposes. Its existence has been influenced by the concoction of alcoholic beverages which adversely affects the traditional alcoholic beverages’ image. These beverages are actually Intellectual Property Rights, IPR-based products of cultural heritage with indications of origin that have characteristics so that they cannot be compared to other countries’ alcoholic beverages, even though current regulations still regulate the opposite. This paper examines the legal protection of Indonesian traditional alcoholic beverages which are also adapted to their characteristics and the influence of Indonesian legal culture on these traditional alcoholic beverages. This research is a normative study with statutory, conceptual, and comparative approach method with South Korea and France as a comparison. Prudent and objective legal protection from the point of view of IPR for traditional alcoholic beverages is expected to develop positive aspects while still anticipating negative ones. This study concludes that Indonesian traditional alcoholic beverages that fulfill 3 unique characteristics can be protected as intangible cultural heritage (public property) or an indication of origin (belongs to local communities), although what is more appropriate now is an indication of origin so that the Government needs to adjust the regulatory design, especially at the national level, according to the indication of origin. AbstrakMinuman alkohol tradisional telah ada di budaya masyarakat Indonesia dengan berbagai tujuan peruntukan. Perkembangan eksistensinya dipengaruhi oleh minuman beralkohol racikan yang memberi pengaruh buruk ke citra alkohol tradisional. Minuman alkohol tradisional sesungguhnya merupakan produk berbasis kekayaan intelektual di bidang warisan budaya dan indikasi asal yang memiliki karakteristik sehingga tidak dapat disamakan dengan minuman beralkohol lainnya, meskipun regulasi yang ada saat ini masih mengatur sebaliknya. Tulisan ini meneliti mengenai pelindungan hukum minuman alkohol tradisional khas Indonesia yang disesuaikan pula dengan karakteristiknya dan pengaruh budaya hukum masyarakat Indonesia terhadap minuman alkohol tradisional tersebut. Penelitian ini merupakan penelitian normatif dengan metode pendekatan perundang-undangan, pendekatan konseptual, serta pendekatan perbandingan dengan Korea Selatan dan Prancis. Pelindungan hukum yang bijak dan objektif dari sudut pandang Hak atas Kekayaan Intelektual (HKI) terhadap minuman alkohol tradisional diharapkan dapat mengembangkan aspek positif dengan tetap mengantisipasi aspek negatifnya. Penelitian ini menyimpulkan bahwa minuman alkohol tradisional khas Indonesia yang memenuhi 3 karakteristik khusus dapat dilindungi sebagai warisan budaya tak benda (milik publik) ataupun indikasi asal (milik masyarakat lokal) walaupun yang lebih tepat untuk diterapkan saat ini adalah indikasi asal sehingga Pemerintah perlu menyesuaikan perancangan regulasi di tingkat pusat sesuai indikasi asal.